Fenton-like oxidation of landfill leachate - Javier Rivas, F. (2003)
The treatment of stabilized leachates by means of Fenton's like reagent [Fe(III)-H2O2] has been studied. It has been demonstrated that the oxidation state of the catalyst does not influence the efficacy of the process in terms of chemical oxygen demand depletion profiles. The abrupt increase in temperature experienced in oxidation experiments involves a wastage of hydrogen peroxide diminishing the fraction of this reagent addressed at removing COD. If temperature is kept constant, the hydrogen peroxide uptake is 10 mg of H2O2 consumed per mg of COD abated (from 15 to 30°C). Working temperatures above 30°C does not lead to additional COD conversion, contrarily, the percentage of wasted H2O2 is increased. A rough economic analysis of the process indicates that this treatment can be a suitable alternative to deal with this type of effluents.